2020
DOI: 10.3389/fneur.2020.583177
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Disease-Specific Oromandibular Dystonia Rating Scale (OMDRS)

Abstract: Background: Oromandibular dystonia manifests with sustained or task-specific contractions of the masticatory, tongue, and/or other muscles in the stomatognathic system. Since its symptoms can vary, it has been difficult to objectively measure disease severity and post-treatment changes. Objective: To develop and validate a comprehensive measurement tool for oromandibular dystonia. Methods: An examiner-rated scale included three subscales for severity, disability, and pain, modified specifically for oromandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 39 publications
0
60
0
2
Order By: Relevance
“…The study compared the “movement-related cortical potentials” (MRCPs) between 6 OMD patients and 8 normal subjects and found that MRCP amplitudes over central and parietal areas for mouth opening and lateral movements were significantly reduced compared to normal subjects, which implies that impaired cortical preparatory process for jaw movements exist in OMD ( 61 ). Although scientists attempted to elucidate the pathophysiology of OMD using several neuroimaging techniques, its etiology remains unclear ( 61 , 62 ). Further research is needed to explore the pathophysiology of OMD to develop better treatments.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The study compared the “movement-related cortical potentials” (MRCPs) between 6 OMD patients and 8 normal subjects and found that MRCP amplitudes over central and parietal areas for mouth opening and lateral movements were significantly reduced compared to normal subjects, which implies that impaired cortical preparatory process for jaw movements exist in OMD ( 61 ). Although scientists attempted to elucidate the pathophysiology of OMD using several neuroimaging techniques, its etiology remains unclear ( 61 , 62 ). Further research is needed to explore the pathophysiology of OMD to develop better treatments.…”
Section: Pathophysiologymentioning
confidence: 99%
“…A case report found c.613T>A (p.F205I) mutation in OMD and this mutation produces frequent inclusions when expressed in cultured cells, a phenotype shared by the Δ E mutant TOR1A, but not wildtype protein ( 68 ). A case-control study found a significant association between rs1182 of TOR1A and BSP ( 62 ). While another study suggested that rs2296793, rs1182, and MtDEL of TOR1A were not associated with BSP ( 42 ).…”
Section: Geneticsmentioning
confidence: 99%
“…Drittens gibt es wenige Bewertungsskalen, um den Schweregrad der OMD und die Veränderungen nach der Behandlung zu beurteilen. Kürzlich wurde eine Bewertungsskala für OMD (oromandibular dystonia rating scale, OMDRS) entwickelt und validiert [101]. Daher ist es wichtig, mehr Patienten mit OMD richtig zu diagnostizieren, zu behandeln und klinische Studien mit einem hohen Evidenzniveau durchzuführen.…”
Section: Schlussfolgerungenunclassified
“…OMD is a focal type of dystonia involving the masticatory and/or lingual muscles. OMD includes jaw closing dystonia, jaw opening dystonia, lingual dystonia, jaw deviation dystonia, jaw protrusion dystonia, and lip dystonia [37,38]. A recent study postulated that OMD has an equal or higher prevalence of cervical dystonia or blepharospasm [62].…”
Section: Effects Of Bont/a On Omdmentioning
confidence: 99%
“…A recent study postulated that OMD has an equal or higher prevalence of cervical dystonia or blepharospasm [62]. The approaches to OMD treatment should be taken seriously not only by neurologists or neurosurgeons, but also by oral and maxillofacial surgeons or dentists [37][38][39]62]. Patients with OMD were successfully treated with BoNT/A.…”
Section: Effects Of Bont/a On Omdmentioning
confidence: 99%